Evaluation of Physical, Processing and Quality Attributes of Cashew Varieties Grown under Odisha Condition - Sethi, S. S.; Panda, P. K.; Sethy, B. K.; Mohanty, Simanta; Jena, Chinmaya; Rout, C. K. (International Journal of Bio-resource and Stress Management, 2026)
A study was undertaken during November, 2021–June, 2022 to evaluate twenty-four varieties of cashew collected from Cashew Research Station, All India Co-ordinated Research Project on Cashew, OUAT, Bhubaneswar. The experiment was laid on experimental design RBD comprises of 24 treatments and 2 replications investigated for the physical, processing and quality attributes which included nut weight, breadth, length, thickness, kernel weight, shelling percentage, kernel count, percentage yield, moisture %, protein, fat, carbohydrate and sugar content of whole kernel. Cashew, an important nut crop in the world market, including India and this influenced adaptation of breeding program for targeting higher yield and profitability with good quality kernel of consumer’s interest. Results indicated that significant differences were observed for various traits for studied cultivars. Highest nut weight (8.33 g), nut length (3.90 cm), nut width (2.76 cm) and nut thickness (19.45 mm) were observed in BPP-8 followed by Jagannath. However, for processing attributes best results observed in Jagannath for characters kernel weight (2.49 g), shelling percentage (32.02), percent yield of whole kernel (85.95%) and kernel count (182) followed by Balabhadra, BPP-8 and Vengrula-7. Balabhadra showed best results for quality attributes like Protein content (21.91%) and fat content (42.87%) while vengurla-7 (H-255) showed best quality attributes like carbohydrate content (22.05%) and sugar content (0.220 %). Out of 24 commercial cashew genotypes BPP- 8 and Jagannath variety exhibited better yield and processing quality.